Analysis of free amino acid composition in fruits of different bayberry (Morella rubra) varieties - ZHU Yifan; WANG Yan; WANG Guoyun; ZHOU Chaochao; JIAO Yun; GAN Kexin; SUN Deli; ZHU Changqing; JIA Huijuan; GAO Zhongshan (浙江大学学报. 农业与生命科学版)
Free amino acids have an impact on the flavor and nutritional values of fresh fruits. The variation of free amino acid compositions and contents in the fruits of 11 different bayberry varieties from Yuyao City, Zhejiang Province, were investigated by Hitachi L-8900 automatic amino acid analyzer. The results showed that the 11 bayberry varieties all contained 17 common free amino acids and one special amino acid γ-aminobutyric acid, and the total contents of free amino acids in the fruits ranged from 338.25 to 827.34 μg/mL. The variations in free amino acid contents among different colored fruits of the bayberry varieties were big. The purple-black and red bayberries, such as ‘Biqi’ and ‘Dongkui’, were the main varieties on the market with the total contents of free amino acids being higher than those of pink and milky white bayberries. The γ-aminobutyric acid content was rich in the 11 bayberry varieties, and its content ranged from 67.05 to 156.32 μg/mL. But there were some differences between different varieties, which indicating that bayberry varieties have differences in nutrition and quality. These results are useful for evaluating the effects of amino acids on fruit flavor and can provide references to the new variety development.